2001
DOI: 10.1161/hc4701.099782
|View full text |Cite
|
Sign up to set email alerts
|

β-Blockers Before Percutaneous Coronary Intervention Do Not Attenuate Postprocedural Creatine Kinase Isoenzyme Rise

Abstract: Background-␤-blocker (BB) use reduces infarct size in spontaneously occurring nonreperfused infarcts but probably does not change infarct size in patients treated with reperfusion therapy. A recent observational study suggested that BB use concurrent with percutaneous coronary intervention (PCI) decreased the risk of creatine kinase (CK)-MB elevation. The cogency of such a conclusion is dependent on the ability to risk-adjust for the multiple differences in patients treated with and without BBs. Methods and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 13 publications
2
20
2
Order By: Relevance
“…23,24 The possible benefit from long-term oral ␤-blocker use was examined in an observational retrospective study that showed a reduction in the incidence of MI in patients who were taking long-term oral ␤-blocker therapy before PCI compared with those who were not. 25 However, a second large retrospective analysis did not confirm this finding, 26 nor did the present study (see Figure 3). In the present study, patients taking long-term oral ␤-blockers had a similar benefit to those who were not, demonstrating the additional benefit of IC propranolol (Figure 4).…”
Section: Wang Et Alcontrasting
confidence: 79%
“…23,24 The possible benefit from long-term oral ␤-blocker use was examined in an observational retrospective study that showed a reduction in the incidence of MI in patients who were taking long-term oral ␤-blocker therapy before PCI compared with those who were not. 25 However, a second large retrospective analysis did not confirm this finding, 26 nor did the present study (see Figure 3). In the present study, patients taking long-term oral ␤-blockers had a similar benefit to those who were not, demonstrating the additional benefit of IC propranolol (Figure 4).…”
Section: Wang Et Alcontrasting
confidence: 79%
“…40 ␤-blockers have been shown in some analyses to reduce periprocedural MI, whereas other analyses have disputed this finding. 41,42 Although markers of inflammation such as hsCRP appear capable of predicting embolization and myonecrosis, other inflammatory markers such as soluble CD40L or myeloperoxidase may prove to be of greater utility. More likely, panels of inflammatory markers measured before PCI would provide greater incremental prognostic ability.…”
Section: Inflammation and Periprocedural MImentioning
confidence: 99%
“…0.001). Conversely, in a study by Ellis et al [29] of 6,200 PCI patients (66% with unstable angina), pre-intervention ␤ -blocker use was not associated with peri-procedural infarction.…”
Section: Infarct Sizementioning
confidence: 84%
“…Chronic pre-intervention oral ␤ -blockers has been reported by some [28] , but not others [29] , to be associated with reduced peri-procedural infarctions in patients undergoing elective PCI. Sharma et al [28] analyzed the outcomes of 1,675 consecutive patients undergoing elective PCI with respect to ␤ -blocker use before the intervention.…”
Section: Infarct Sizementioning
confidence: 96%